METAFORA DALAM LIRIK LAGU KOKORO NO TOMO KARYA ITSUWA MAYUMI - Akhmad Saifudin (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2012)
This article discusses the meaning of the metaphor contained in the Japanese song’s lyrics. With the use of metaphor analysis "Knowles and Moon" (2006), this research examines twelve metaphors from the data source entitled Kokoro no Tomo. The aim of this study is to describe the use and meaning of the metaphor used by song’s writer. Song’s lyric is like a poem which always contains aestetice matters. It represents the expression of the writers concerning his perspective about something. To understand a song’s lyric of metaphor, we have to examine the relationship between the literal meaning and the meaning of metaphor or contextual meaning. It can be concluded that metaphor is used by writer to describe his’ real meaning’ that can not be described with ‘ordinary’ words.